20 Cardioprotection During Chemotherapy: A Case Study to Understand Intracellular Mechanisms to Combat the Cardiotoxicity of Sunitinib. (19th January 2014) - Sandhu, H; Cooper, S; Eckert, M; Pisula, L; Chinweike, C; Gharanei, M; Maddock, H L
Abstract : Tyrosine Kinase inhibitor Sunitinib mediates its apoptotic anti-cancer effects by inhibiting intracellular signalling involved in tumour angiogenesis and cell proliferation. Unfortunately Sunitinib has revealed unwanted cardiotoxicity side-effects and investigations into cardioprotective adjunct therapy agents are critical. A3 adenosine receptor agonists (A3AR) have been shown to have powerful cardioprotective effects against myocardial injury (MI). We studied the effect of A3AR agonist IB-MECA in preventing MI following Sunitinib treatment and assessed whether IB-MECA jeopardized the anti-cancer/apoptotic effect of Sunitinib in cancer cells. The associated intracellular signalling pathway through Protein Kinase C α/β (PKC α/β) and microRNA expression signatures were investigated. HL60 cells were incubated with increasing concentrations of Sunitinib (0.1-10 μM) ± IB-MECA (1 nM) for 24h and cell viability (CV) was assessed. Langendorff hearts underwent Sunitinib (0.3 μM) ± IB-MECA (1 nM) treatment and MI assessment. Phosphorylated expression levels of Protein Kinase C α/β were assessed by Western Blot analysis and rtPCR analysis revealed the microRNA expression signature. Sunitinib decreased HL60 cell viability and increased MI compared to vehicle (Vehicle: CV = 102.0 ± 1.4%; MI = 8.2 ± 3.6%; Sunitinib: CV(10 μM) = 43.2 ± 6.3%, p = 0.02; MI(0.3 μM) = 30.1 ± 1.5%, p < 0.001). Addition of IB-MECA did not alter the apoptotic effect of Sunitinib, however, IB-MECA attenuated the Sunitinib-induced MI (Sunitinib + IB-MECA: CV(10 μM) = 37.8 ± 6.4%; MI(0.3 μM) = 20.4 ± 2.8%, p < 0.01). The IC50-values of Sunitinib ± IB-MECA did not change significantly (Sunitinib IC50-value = 8.4 ± 1.3; Sunitinib + IB-MECA IC50-value = 7.0 ± 1.6) (n = 5–6). This study reveals for the first time that A3AR activation improves myocardial survival by attenuating Sunitinib induced MI without interfering with the anti-tumour efficacy of Sunitinib. A3AR associated signalling pathways could be important in the development of adjunctive chemotherapy treatment.